Photography Training and Writing Skills for Meaning/Photo Messages with Communicative Language fo Excellent Nurul Ikhlas High School Students - Cindi Adelia Putri Emas; Ermi Rosmita (Outline Journal of Community Development, 2024)
Community service activities with the theme "Photography Training and Writing Skills for Photo Meanings/Messages with Communicative Language for Students of Excellent Nurul Ikhlas High School" aims to improve the ability of students of Excellent Nurul Ikhlas High School, Tanah Datar in capturing moments that have human interest value through photography and composing the right words to be able to provide deep meaning/messages to the photos that have been created. This community service activity also aims to motivate students to further explore their creativity, especially in improving visual experience and improving the ability to narrate well-recorded memories. The methods used in this community service include two stages, namely the training stage (lecture) and direct practice of photographing and creating meaning/messages from the photos. From the results of the training, it can be seen that this community service activity is able to increase insight, improve technical abilities, and skills, as well as students' creativity in improving hard skills and soft skill in the field of photography and writing meaning/messages from photos that have been taken using communicative language.